Microencapsulation of Plant Phenolic Extracts Using Complex Coacervation Incorporated in Ultrafiltered Cheese Against AlCl3-Induced Neuroinflammation in Rats - Soliman, Tarek N.; Mohammed, Dina Mostafa; El-Messery, Tamer M.; Elaaser, Mostafa; Zaky, Ahmed A.; Eun, Jong-Bang; Shim, Jae-Han; El-Said, Marwa M. (Frontiers in Nutrition, 2022)
Plant-derived phenolic compounds have numerous biological effects, including antioxidant, anti-inflammatory, and neuroprotective effects. However, their application is limited because they are degraded under environmental conditions. Microencapsulation may be an alternative to mitigate this problem. Red beet (RB), broccoli (BR), and spinach leaf (SL) phenolic extract were encapsulated by complex coacervation. The characteristics of complex coacervates (zeta potential, encapsulation efficiency, FTIR, and morphology) were evaluated. RB, BR, and SL complex coacervates were incorporated into an ultra-filtered (UF) cheese system. The chemical properties, pH, texture profile, microstructure, and sensory properties of UF-cheese with coacervates were investigated. Fifty-four male Sprague-Dawley rats were used; 48 rats were administered an oral dose of AlCl3 (100 mg/kg body weight/d). The nutritional and biochemical parameters, including malondialdehyde, superoxide dismutase, catalase, reduced glutathione, nitric oxide, acetylcholinesterase, butyrylcholinesterase, dopamine, 5-hydroxytryptamine, brain-derived neurotrophic factor, and glial fibrillary acidic protein, were assessed. RB, BR, and SL phenolic extracts were successfully encapsulated. RB, BR, and SL complex coacervates had no impact on the chemical composition of UF-cheese. The structure of RB, BR, and SL complex coacervates in UF-cheese was the most stable. The UF-cheese hardness was progressively enhanced with RB, BR, and SL complex coacervates. The sensory characteristics of UF-cheese samples received good scores and were viable for inclusion in food systems. Additionally, these microcapsules improved metabolic strategies and neurobehavioral systems and enhanced the protein biosynthesis of rat brains. Both forms failed to induce any severe side effects in any experimental group.